Adaptive Planning, Monitoring, and Evaluation for Long-Term Impact: Insights From a Water Supply Case in Bangladesh - Versteeg, Niki; Hermans, Leon M.; Ahrari, Sara; Van De Walle, Bartel A. (Frontiers in Water, 2021)
Most water and development interventions aim to contribute to long-term sustainable impacts. Given the uncertainties involved in these longer-term water development projects, adaptive planning approaches hold promise to connect planning, implementation and evaluation. Recent innovations report promising results, but find limited wide-spread practice due to a relatively large distance from current operational realities. Therefore, in this article we set out to investigate the real-world benefits and barriers for adaptive planning, monitoring and evaluation as a tool for water development interventions. To do so, we have stripped the advanced theoretic adaptive planning approach to its essentials, for exploration in an ongoing water development project. Application of the resulting three essential adaptive planning steps to a water development project in Khulna, Bangladesh shows that these steps are feasible and can support a more adaptive planning and management. In particular, they have helped to surface critical assumptions and uncertainties, as well as associated adaptation actions for the case. These were related to spatial development, water quality, finance, and management capacity. However, results also show that the actual use of the proposed steps is likely to be hindered by strategic misrepresentation. Our findings suggest this as an additional and more fundamental barrier to the widespread use of adaptive planning practices. We reflect on this barrier of strategic misrepresentation and on possible mechanisms to counter it, in order to enable water development actors to make their planning and evaluation arrangements more adaptive.